The marketing book - Baker, Michael J.; Hart, Susan (Butterworth-Heinemann, 2008)
The 6th edition of the best-selling Marketing Book has been extensively updated to reflect changes and trends in current marketing thinking and practice. Taking into account the emergence of new subjects and new authorities, Michael Baker and the new co-editor Susan Hart have overhauled the contents and contributor lists of the previous edition to ensure this volume addresses all the necessary themes for the modern marketer. In particular, the 'Marketing Book' now looks at broader range of international issues with a broader group of international contributors. Based, as in previous editions, on seminal articles form thought leaders in each subject the 'Marketing Book 6th edition' is bursting with salient articles. It amounts to an all-embracing one-volume companion to modern marketing thought, ideal for all students of marketing. .6th edition of a seminal overview of the latest thinking in Marketing .A carefully commissioned set of pieces from leaders in each major field reviewing the state of their discipline .Widely referred to by faculty and graduate students.